Vpliv družinskega okolja na revščino in socialno izključenost otrok - Narat, Tamara (Socialno delo, 2010)
Poverty means violation of human rights. In the case of children, having long-term consequences not only for individuals but also for the society in general.The analysis of internationally comparable indicators of social exclusion (Laekens indicators) shows that the level of poverty risk is highest in single parent families with both unemployed parents, and in families where both parents have a lower education level. The social exclusion of children is reflected as material deprivation (holidays, owning a computer, food, living conditions, etc.) and as poorer education of children,because children whose parents are poor often have worse learning results and consequently reach a lower level of education. In Slovenia, there is relatively low children's poverty risk level but nonetheless numerous improvements in some areas are necessary as children's rights are far from being implemented.
Keywords: družinsko okolje; revščina; child; otroci; socialna izključenost; izobrazba